BUDAYA HUKUM INDONESIA DALAM MENGHADAPI PERKEMBANGAN KASUS KORUPSI DI INDONESIA - Rosisca, Napoleon; Anriyani, Dian; Herianto, Fandy; Sari, Elsi Kartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Corruption is a serious problem in Indonesia that adversely affects economic growth, weakens law enforcement and reduces public trust in government institutions. Indonesia's legal culture is influenced by factors such as traditional values, religion, and complex social systems. The main problem in this paper is how the implementation of laws related to corruption is in line with the legal culture that exists in Indonesia and how the substance of the law is able to maintain awareness of corrupt behavior in Indonesia. The research method used is normative legal law and how to collect data with literature studies, qualitative analysis and how to draw conclusions with the deductive method. The conclusion in this research is that the implementation of law in eradicating corruption in Indonesia still faces great challenges due to the influence of the existing legal culture and public awareness of corruption is still low even though there are laws governing it, inconsistent law enforcement, lack of socialization and a social culture that considers corruption to be commonplace which is the main obstacle. Without a comprehensive change in the legal system and culture, the eradication of corruption will be difficult to succeed. Keywords: Legal Culture, Corruption, Law Implementation